Structure-Function Analysis of SUV39H1 Reveals a Dominant Role in Heterochromatin Organization, Chromosome Segregation, and Mitotic Progression - Melcher, Martin (American Society for Microbiology, 2000)
SUV39H1, a human homologue of the Drosophila position effect variegation modifier Su(var)3-9 and of the Schizosaccharomyces pombe silencing factor clr4, encodes a novel heterochromatic protein that transiently accumulates at centromeric positions during mitosis. Using a detailed structure-function analysis of SUV39H1 mutant proteins in transfected cells, we now show that deregulated SUV39H1 interferes at multiple levels with mammalian higher-order chromatin organization. First, forced expression of full-length SUV39H1 (412 amino acids) redistributes endogenous M31 (HP1β) and induces abundant associations with inter- and metaphase chromatin. These properties depend on the C-terminal SET domain, although the major portion of the SUV39H1 protein (amino acids 89 to 412) does not display affinity for nuclear chromatin. By contrast, the M31 interaction surface, which was mapped to the first 44 N-terminal amino acids, together with the immediately adjacent chromo domain, directs specific accumulation at heterochromatin. Second, cells overexpressing full-length SUV39H1 display severe defects in mitotic progression and chromosome segregation. Surprisingly, whereas localization of centromere proteins is unaltered, the focal, G(2)-specific distribution of phosphorylated histone H3 at serine 10 (phosH3) is dispersed in these cells. This phosH3 shift is not observed with C-terminally truncated mutant SUV39H1 proteins or with deregulated M31. Together, our data reveal a dominant role(s) for the SET domain of SUV39H1 in the distribution of prominent heterochromatic proteins and suggest a possible link between a chromosomal SU(VAR) protein and histone H3.